TRUNCATIONS OF THE RESPONSE REGULATOR AGRA INHIBIT STAPHYLOCOCCUS AUREUS QUORUM SENSING - Ruyter, Alexandra L. (My University, 2013)
Virulence in Staphylococcus aureus is mediated by the accessory gene regulator (agr) quorum sensing system. This regulatory system is activated by a secreted thiolactone peptide termed autoinducing peptide (AIP) and its receptor histidine kinase, AgrC. Interaction of extracellular AIP with a cognate AgrC receptor generates an intracellular signal that is transduced by conformational changes and phosphorylation events in a two-component sensor histidine kinase system. At the heart of the agr quorum-sensing cascade lies the two-component histidine kinase, AgrC, and the response regulator protein, AgrA. Interaction of AgrC and AgrA, and the resulting phosphotransfer event results in expression from the divergent promoters P2 and P3, inducing expression of the master quorum-sensing regulator RNAIII and upregulating the agr operon respectively. Signal transduction systems function as intracellular information-processing pathways that link sensation of external stimuli to specific adaptive processes. In S. aureus , these include the up-regulation of virulence factors and hemolysis production, biofilm formation, and colonization-based regulation of surface proteins and adhesion factors. As such, the interactions of these systems have become key targets in the design of small inhibitor compounds.
Through the creation of a protein truncation series, we proposed the development of a small protein for the inhibition of key protein-protein interactions involved in S. aureus agr two-component signaling. Herein, we demonstrate the efficacy of these protein truncations as dominant negative inhibitors of AgrC:AgrA interactions, likely acting as a dominant phosphoacceptor in place of endogenous AgrA. We provide evidence of this function through in vitro hemolysis assays and phosphate-detection based gel electrophoresis.
Keywords: Staphylococcus aureus; quorum sensing; dominant negative decoy; peptide mimetic; inhibition; Medical Sciences; Medical Sciences